Use of bio-protective cultures to improve the shelf-life and the sensorial characteristics of commercial hamburgers. Issue 2 (July 2015) - Comi, Giuseppe; Tirloni, Erica; Andyanto, Debbie; Manzano, Marisa; Iacumin, Lucilla
Abstract The use of mixtures of bio-protective cultures, like Lactobacillus sakei subsp. carnosus/L. sakei + Staphylococcus xylosus (1/1 ratio), Lactococcus lactis spp. lactis/L. sakei + S. xylosus (1/1 ratio), and L. sakei subsp. carnosus/L. sakei + S. xylosus (1/2 ratio), inoculated in beef hamburger packaged in modified atmosphere and stored at 4 ± 2 °C, determined a better microbiological and chemical-physical quality of the products. In particular, they inhibited the growth of Brochothrix thermosphacta resulting in no white slime on the products as well as they determined a low concentration of total volatile basic nitrogen (TVB-N). Moreover, the bio-protective cultures influenced the flavour and the odour of the hamburgers. For this reason, the shelf life of the products added with starter cultures could be extended up to 12 days.